Effects of Blackboard Resources Utilization on Students' Performance in Molecular Biology Course. (28th October 2020) - Kandel, B P; Hackfeld, M; Zhang, J; Guo, F
Abstract: Introduction/Objective: Molecular diagnostics utilizes structural and functional fundamentals of molecular biology and finds its scope in clinical education for disease diagnosis and monitoring, and evaluation of non-disease status. Time and financial constraints make molecular biology education challenging for both teachers and students. Advances in information technologies have helped teachers to provide a rich resource to students which if properly utilized is expected to generate better teaching-learning outcomes. However, the pattern of utilization of digital resources by students and its impact on their performance is still unknown. The aim of this study was to assess students' behavior to Blackboard resource utilization and its impact on their performance in molecular biology course. Methods: We conducted a retrospective cross-sectional study including all the 46 students (9 graduate and 37 undergraduate students; 14 distant and 32 regular students) enrolled for molecular biology course in the year 2017 and assessed the associations between blackboard resource visits and students' final weighted total grades. Blackboard resource visit variables included "Tegrity" viewing duration, viewing times, and contents viewed ("My Grades", "Announcement", "Discussion", "Contacts", "Content Item"). Results: Among all students, the most and least visited contents were "Content Item" (261 average hits) and "Contacts" (1.28 average hits), respectively with similar patterns of the visit among all student sub-categories. The longest average Tegrity viewing duration (25 hours) and the highest average Tegrity viewing times (56 hits) were noted among undergraduate distance students. The average grade was higher among graduate students than undergraduate students. The overall blackboard resource visit and the individual category visit among graduate and undergraduate students had no association with students' final weighted scores. Conclusion: Our findings have important implications for the utility of blackboard resources among graduate and undergraduate clinical laboratory science students. Similar assessments including students from many different years are recommended to generate more accurate evidence.